Efektivitas Mediasi terhadap Penyelesaian Perkara Perceraian di Pengadilan Agama - Ach. Muzamzil; Rudi Hermawan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research aims to find out clearly how effective mediation is in religious courts, whether implementing direct or virtual mediation, in handling divorce cases, and it can be concluded that direct mediation in religious courts is more effective than indirect (virtual) mediation. All civil cases must be resolved through a mediation process first, as well as cases in religious courts, even with technological developments. Perma No. 1 of 2016 which provides the option of mediation, which must be carried out in person, can carry out the mediation process indirectly (virtually) for parties who are unable to attend in person. The method used is a descriptive research method of analysis of mediation theory and its implementation in religious courts. This study found a number of findings that can provide significance for the development of knowledge in the field of religious court procedural law.